Clinical case of infectious mononucleosis with facial neuropathy - T. E. Shvets; E. A. Gashina; E. F. Lobova (LLC "Diagnostics and Vaccines", 2024)
Infectious mononucleosis is a current problem of pediatric practice, which tends to increase the incidence in the Russian Federation and other countries. Liver dysfunction of varying severity in infectious mononucleosis occur with a frequency of 17-90% of cases while Epstein-Barr neuroinfections of viral etiology occur in no more than 5% of patients. This article presents a clinical case of infectious mononucleosis with liver damage and right facial neuropathy in a 15-year-old child.